Marabou Stork Leptoptilos crumenifer breeding in the greater Gorongosa landscape, Mozambique. (1st October 2020) - Stalmans, Marc; Botha, Andre; Scott, Teague; Kaltenecker, Gregory; Monadjem, Ara
Abstract : The Marabou Stork Leptoptilos crumenifer is a large wading bird that occurs extensively throughout sub-Saharan Africa in savanna and wetland habitats. Despite its widespread occurrence in southern Africa, the number of known breeding localities and the numbers of nests are limited. We report on large, dispersed nesting colonies in the greater Gorongosa landscape in central Mozambique. We counted the number of active Marabou nests in Gorongosa National Park and adjoining areas by conducting annual aerial (helicopter) surveys between 2016 and 2019. The Muaredzi colony within Gorongosa National Park has been expanding annually from 82 active nests in 2016 up to 258 nests in 2019. Similarly, the Mussicadzi colony has increased from five nests in 2016 to 81 nests in 2019. A total of 373 active nests were recorded in 2019 in Gorongosa National Park. Since 2017, a small number of additional nests were also observed in the Coutada 11 and Coutada 12 hunting areas, adjacent to Gorongosa. The total count for the greater Gorongosa landscape was 380 active nests in 2019. This represents the first formal record of what appears to be the single largest breeding assembly of Marabou Storks south of the Zambezi and Cunene Rivers. The observation of a significant number of active Marabou nests in the greater Gorongosa landscape has important conservation implications.